Forensic Stylistic Analysis of Jakarta Man’s Suicide Note - Lubis, Ezra Rumatha; Tarigan, Agit Seprina; Simangunsong, Anisyah S.; Ambarita, Mariyanti; Rangkuti, Rahmadsyah (English Lecturers and Teachers Association (ELTA), 2024)
Forensic stylistics, a crucial tool in crime-solving, analyzes linguistic features to reveal authorship, truthfulness, and narrative structure. This study applied forensic stylistic analysis to a Jakarta man's suicide note, employing Prokofyeva's theory. The analysis revealed insights into the author's psychological state and motivations, echoing findings by Maulida et al. Key elements examined include clear reasoning, emotional expressions, and the presence of positive, negative, and cognitive emotions. The note's structure, grammar, punctuation, cultural context, and vocabulary choices offer a comprehensive view of the author's mental turmoil. By extending Prokofyeva's framework to a different cultural context, this research demonstrates the versatility and applicability of forensic stylistics in deciphering suicide notes across diverse populations. The study underscored the importance of linguistic analysis in understanding the complex emotions and cognitive processes behind suicide, providing valuable information for criminal investigations and psychological assessments. Through this meticulous examination, the research contributes to the broader understanding of forensic stylistics and its role in uncovering the deeper layers of meaning within final messages, offering a poignant glimpse into the author's state of mind before their tragic decision. Keywords : Forensic_stylistic; Suicide_ note:Linguistic_features